Electronic Description of the Photophysics of Homo‐ and Heterodinuclear Cyclometallated Iridium and Rhodium Complexes. Issue 5 (3rd February 2017) - Seth, Sourav Kanti; Mandal, Soumik; Srikanth, K.; Purkayastha, Pradipta; Gupta, Parna
Abstract : Photophysical properties of homodinuclear complexes1 (Ir), 2 (Rh) and heterodinuclear complex3 (Ir–Rh) have been discussed in solution and in the solid state with the help of quantum chemical calculations by combined DFT‐TDDFT methods. Quantum calculations on these three complexes indicate the participation of metal‐to‐ligand and ligand‐to‐ligand charge transfers to the lowest energy absorptions, and electron transitions from the cyclometallating ligand to the ancillary ligand. The emission behaviour in the solution and solid state confirm the participation of the triplet state as obtained from quantum chemical calculations. It is also noted that the emission behaviour in the mixed‐metal complex is controlled by the iridium metal centre. The ground state electronic interactions between the metal centres studied by electrochemistry are weak interactions, however, energy transfer in the excited state is facile across the bridge. Abstract : A perceptive insight into the ground and excited state electronic interactions in homo‐ and heterodinuclear cyclometallated iridium(III) and rhodium(III) complexes has been discussed in detail from photophysical, electrochemical and DFT‐TDDFT studies. The ground state energy transfer is much weaker than the excited state across the bridging ligand.